2013
DOI: 10.1007/s11739-013-1007-x
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced angioedema: experience of Italian emergency departments

Abstract: Acute angioedema represents a cause of admission to the emergency department requiring rapid diagnosis and appropriate management to prevent airway obstruction. Several drugs, including angiotensin-converting enzyme inhibitors (ACE-I), nonsteroidal anti-inflammatory drugs (NSAIDs) and oral antidiabetics, have been reported to induce angioedema. The aim of this prospective observational study conducted in a setting of routine emergency care was to evaluate the incidence and extent of drug-induced non-histaminer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Less commonly, an increased risk of nonhistaminergic angioedema has been associated with other classes of drugs, including nonsteroidal anti-inflammatory drugs (NSAIDs), antibiotics, and angiotensin receptor blockers (ARBs) [7, 32]. NSAID-related angioedema is estimated to occur in 0.1–0.3% of persons exposed to NSAIDs [33, 34].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Less commonly, an increased risk of nonhistaminergic angioedema has been associated with other classes of drugs, including nonsteroidal anti-inflammatory drugs (NSAIDs), antibiotics, and angiotensin receptor blockers (ARBs) [7, 32]. NSAID-related angioedema is estimated to occur in 0.1–0.3% of persons exposed to NSAIDs [33, 34].…”
Section: Reviewmentioning
confidence: 99%
“…Between 2280 and 5000 visits to US EDs each year are attributable to hereditary angioedema (HAE) [5, 6], accounting for a rate of 1.87:100,000 ED visits [5]; however, these figures may underrepresent the true level of angioedema-related ED use [2, 5, 6]. Similar data from Italy suggest that 0.37% of all ED visits are related to angioedema [7], and a recent Canadian study estimated that 1:1000 ED visits are angioedema related [8]. Finally, a survey in the UK revealed that 30% of patients with hereditary or acquired angioedema have visited the ED [9].…”
Section: Introductionmentioning
confidence: 99%
“…They represent the most frequent cause of hypersensitivity drug reactions (HDRs) in adults [2,3] and are also frequent in children [4][5][6]. Recently, a new classification of HDRs to NSAIDs has been published, stratifying patients according to the time between drug intake and reaction (immediate or delayed), the mechanisms involved [selective or cross-intolerance (CI)], and clinical symptoms [7].…”
Section: Introductionmentioning
confidence: 99%
“…lı olduğu bildirilmektedir. [3][4][5] Acil vizitlerinin herhangi bir nedene bağlı anjioödemilişkili olma oranı İtalya' da: 4/1.000, Kanada' da ise 1/1.000 olarak saptanmıştır.…”
unclassified